KEANEKARAGAMAN JENIS MAMALIA DI CAGAR ALAM BUKIT BUNGKUK KABUPATEN KAMPAR PROVINSI RIAU - Pangestu, Wibowo; Yoza, Defri Yoza; Darlis, Viny Volcherina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Forests play an important role in regulating the hydrological system, as an absorber of carbon dioxide and an oxygen producer so that forests are also known as the lungs of the world. Forest is a habitat for various types of living things, both flora and fauna. Forests play an important role for human life and other organisms that live in it such as animals and plants. Until now, the function of forests cannot be replaced by any technology. This study aims to determine the diversity of mammal species in the Bukit Bungkuk Nature Reserve, Kampar Regency, Riau Province.Data collection methods used were line transects and traps which consisted of primary and secondary data. The data analysis techniques used were Species diversity and Species richness. Based on the results of data processing, the analysis used species diversity in the Bukit Bungkuk Nature Reserve area, the index for the diversity of mammals in the medium category with an average index of 2,53. Meanwhile, analysis with species richness shows that the average species richness index contained in the observation paths is in the medium category with the index magnitude of 3,11. Based on the results obtained, it is concluded that the diversity of mammal species in the Bukit Bungkuk Nature Reserve found 15 mammal species in 11 families. The diversity index of mammals in the Bukit Bungkuk Nature Reserve shows a moderate index and the index value of mammal species richness in the Bukit Bungkuk Nature Reserve is moderate.Keywords: Forest, diversity of mammals, species richness, Bukit Bungkuk Nature Reserve